MEDIA KOMUNIKASI DAN BUDAYA VISUAL: Studi Kasus Baliho Gerakan Tolak Reklamasi Teluk Benoa - Jayanegara, I Nyoman (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
The rejuvenating movement of Benoa Bay reclamation in Bali begins in mid-2013 in the form of massive demonstrations, oral and written statements of attitudes, art attractions, music concerts, and online petitions. Visual communication media in various forms did not escape the dissemination of the movement of such rejection. Giant Banner are one of the most vibrant visual communication media used in voicing the denial movement. Those Giant Banners display the same visual pattern, which presents an illustration of Balinese culture that is considered to represent the movement. These visual patterns are designed without regard to the standard rules in design, seemingly playful, free, and just excite the designers themselves. The visual strategy presented indirectly gives a distinctive feature of the movement so as to produce a new visual culture through the visual communication media used.